The Role of Giri Swara Radio in Suppressing Covid-19 Rates in Wonogiri Regency - Mami Eva Novayani; Pawito Pawito; Agung Satyawan (Journal of International Conference Proceedings, 2022)
The Covid-19 pandemic is still threatening all around us. Corona Virus Disease 2019 or COVID-19 is an infectious disease caused by SARS-CoV-2. The government is trying to educate the public to prevent and treat Covid-19 sufferers. One of the mass media to educate the public is through local public broadcasting radio (LPPL). Radio has an important role to convey information, educate, entertain and social control. This study formulates the role of Giri Swara Radio in suppressing Covid-19 in Wonogiri Regency. This research uses a qualitative approach. Researchers obtained primary data through interviews and field observations. While secondary data is collected through books, articles and websites. The results of the study explain that radio as a communication medium has an important role in educating the public through its various programs. These educational efforts also contributed to reducing the number of Covid-19 in Wonogiri. Several programs of Giri Swara Radio to educate the public include Health Talks and Family Talks.Â Keywords: Role, Radio, Covid-19, Media